Association between the oxidative balance score and testosterone deficiency in males: a cross-sectional study - Zhuge, Ze; Zheng, Kaihui; Ji, Xiaojun; Wang, Xiaobo; Zhang, Xuena (Frontiers in Nutrition, 2025)
BackgroundTestosterone deficiency is a prevalent condition among males and warrants greater attention. The balance between oxidative and antioxidant capacity plays a critical role in testosterone deficiency.MethodsThis study conducted a secondary analysis using data from three cycles of the National Health and Nutrition Examination Survey (2011–2016). The oxidative balance score (OBS) and testosterone levels were derived from interview data and laboratory measurements. Weighted logistic regression was employed to explore the relationship between OBS and testosterone deficiency. Subgroup analyses, sensitivity analyses, and p-value for interaction were also performed.ResultsThe analysis encompassed a cohort of 3,578 participants who met the eligibility criteria. The prevalence of testosterone deficiency among participants was 23.69%. OBS was inversely correlated with testosterone deficiency, with each unit increase in OBS associated with a 3% reduction in the risk of testosterone deficiency (OR, 0.97; 95% CI, 0.95 to 0.99). The highest OBS group exhibited a 38% lower risk of testosterone deficiency (OR, 0.62; 95% CI, 0.40 to 0.96) Compared to the lowest OBS group. Furthermore, lifestyle OBS was also negatively correlated with testosterone deficiency. In, subgroup analyses, the inverse association between OBS and testosterone deficiency was most pronounced in subgroups characterized by educational background beyond high school, PIR > 3, and absence of hypertension or diabetes.ConclusionHigher OBS was inversely correlated with testosterone deficiency in males. This study underscores the importance of comprehensive antioxidant approaches, particularly lifestyle OBS, in male testosterone deficiency.